Metrics for short-term coastal characterization, protection and planning decisions of Sentina Natural Reserve, Italy. (15th February 2021) - Acciarri, A.; Bisci, C.; Cantalamessa, G.; Cappucci, S.; Conti, M.; Di Pancrazio, G.; Spagnoli, F.; Valentini, E.
Abstract: Geomorphological and sedimentological surveys of the emerged and submerged beach-dune system are fundamental for a successful management and protection strategies for coastal planning and development. In particular, these surveys can reveal if coastal areas are affected by erosion, pollution and loss of habitats under the seasonal anthropic pressure related to tourism, leisure and professional fishing, urbanisation and/or other activities impacting the coastal marine resources. In the present study we discuss the results of the multidisciplinary monitoring activities carried out within the Sentina Natural Reserve (Municipality of San Benedetto del Tronto, Adriatic side of Central Italy, at the south-eastern end of the Marche Region) proposing an exportable methodological approach. Due to the absence of buildings, the study area has not been considered in the coastal protection plan by regional and local authorities and, as a consequence, it is currently exposed to severe coastal erosion, the rate of which has been more precisely determined during the present study. This monitoring testifies that most of the seaward surface of the beach disappeared resulting in a general set back of the whole beach environment. In the last decades, several restoration strategies have been adopted to protect and restore the dunes and the back dunes habitats and the municipality also carried out an emergency action to nourish the beach, including the use of sand dredged from the nearby city harbor. With this sediment management approach, a tradeoff between safety of navigation of harbor inlet and habitat conservation of Natural Reserve have been reached, since beach nourishment can reduce coastal vulnerability and risk, even though its sustainability in the long term is still debated. Graphical abstract: Image 1 Highlights: Beach-dune system are complex and dynamic environment. Ephemeral from the geological point of view but important from ecological and economical perspective. Coastal system characterisation and monitoring. Beach-dune dynamic and resilience. Sediment management for conservation of coastal habitat (dune) and adaptation strategies.